Questioning the Research on Early Career Teacher Attrition and Retention - Schaefer, Lee; Long, Julie S.; Clandinin, D. Jean (Alberta Journal of Educational Research, 2012)
In this paper, we consider scholarly work on early career teacher attrition, and retention, from 1999 to 2010. Much of the literature has framed attrition as either a problem associated with individual factors (e.g., burnout), or a problem associated with contextual factors (e.g., support and salary). Some recent conceptualizations consider early career teacher attrition as an identity- making process that involves a complex negotiation between individual and contextual factors. On the basis of our review, we suggest the need to shift the conversation from one focused only on retaining teachers, toward a conversation about sustaining teachers. This shift offers the possibility of new insights about teacher education and about the kinds of spaces needed on school landscapes to sustain and retain beginning teachers. Cet article porte sur les travaux académiques évoquant l'attrition et la rétention des enseignants en début de carrière entre 1999 et 2010. Une part importante de la littérature présente l'attrition comme un problème associé à des facteurs individuels (par ex. épuisement professionnel) ou bien à des facteurs contextuels (par ex. appui et salaire). Selon certaines conceptualisations récentes, l'attrition d'enseignants en début de carrière serait un processus de formation identitaire impliquant des négociations complexes entre l'individu et des facteurs contextuels. À partir de notre analyse, nous évoquons le besoin de s'éloigner des conversations portant exclusivement sur le besoin de retenir les enseignants pour discuter plutôt de soutien aux enseignants. D'un tel changement peuvent découler de nouvelles idées sur la formation des enseignants et le type de milieux scolaires nécessaires pour appuyer et retenir les enseignants en début de carrière.